Draft Annual Plan 2011-2012 - Planning Commission (Planning Commission, 2011)
The State of Jharkhand was created as 28th State of the Indian Union by the Bihar Re-organization Act on 15th November 2000, the birth anniversary of the legendary Bhagwan Birsa Munda. It comprises of the forest tracts of Chhotanagpur plateau and Santhal Paragna. It is bounded by Bihar on the North, Orissa on the South, Chhattisgarh on the west and West Bengal on the East. The State covers 79.70 lakh ha. area (2.42% of the geographical area of the country) with a population of 269 millions (as per Census 2001), the state accounts for 2.6% of the total population of the country. It has sizeable Tribal population (26.3%). Topography of the State is mostly undulating, hilly and sloping with mountains, forests, river basins and valleys.
Planning and Development Department Government of Jharkhand